Faire bonne expression : prise de parole et formation de la pensée en philosophie pour enfants - Samuel Nepton (Recherches en Éducation)
This article aims to present conditions that must be respected by the teacher during a philosophy for children workshop so that the participants’ speeches contribute to the formation of thinking. Indeed, this educational approach which, in recent years, has seen its popularity spread throughout the world, is reversing traditional pedagogies in education by placing the child at the very center of the classroom - literally as well as figuratively. This revolution can be explained by the recognition of an intimate and necessary link between speech, dialogue and thinking. It will be explained in these pages how reflection is intrinsically linked to the expression and how, in return, this expression also implies a double risk for children. Therefore, it will be explained how an education aimed at the formation of thinking should make sure to provide children with an environment in which they can dare to express themselves. However, it will also be presented how speaking is not enough in itself for the formation of thinking. Therefore, rather than just letting children express themselves, the role of the adult should be to challenge them to think by making sure that this speech meets certain conditions such as taking the form of an inquiry and allowing the mobilization of intellectual skills.